CGIAR and Healthy Landscapes - Rijsberman, Frank (CGIAR Consortium, 2014)
Presentation by Frank Rijsberman, CEO, CGIAR Consortium at the Global Forum for Innovations in Agriculture, Abu Dhabi, February 4, 2014